A educação católica por meio do impresso: análise da edição reformulada de 1964 do primeiro catecismo da doutrina cristã - Aline Marie De Simone (2023)
The present dissertation is part of the discussion about the religious printed matter of wide circulation. It focuses on analyzing the reformulation of the Primeiro Catecismo da Doutrina Cristã (First Catechism of the Christian Doctrine) in 1964, published by Editora Vozes (Voices Publishing House). The original text was elaborated in 1903 to uniform the teaching of Christian doctrine in a unique and official text. It has been published over decades with a few variations in graphic format and content. The mobilized sources were different printed editions published throughout the 20th century, catalogs from Editora Vozes, also newspapers and magazines. The changes, words, and ideas that stayed and motivations for the reformulation were identified through comparative document analysis to understand the educational action through this printed matter. To this end, the analyses were directed to the production and content of catechisms, dialoguing with authors of the History of Prints and Books, such as Chartier (1990; 2002; 2010; 2011) and Darnton (1990; 2010). We related the assumptions discussed by Eliade (1992a) in analyzing of this content. They enabled us to understand three fundamental principles that the catechism aimed to spread to the reader: “to know” the Christian doctrine, “to act” as a Christian, and “to convince” other people to incorporate the customs and precepts of the Catholic Church into their lives. It was also possible to verify different ways of reading the reformulated catechism and the possibilities of formations that it made possible. The Second Vatican Council has influenced the reformulation of this catechism because of religion and educative discussions. The Council has kept tradition and, at the same time, inserted itself into a dynamic catechesis that intended to involve more faithful to the Catholic Church. The analysis of the First Catechism of Christian Doctrine, published by Editora Vozes in 1964, allowed us to identify that the changes made also corresponded to a logic aimed at increasing sales of this title and other materials indicated as complementary resources that allowed different ways of using the catechism, demonstrating that the formation intended by the same form can suffer variations. The study helped to understand Catholic movements to integrate and maintain their space in Brazilian society through educational prints in the 20th century. They formed customs, and ways of acting and they are efficient in the project to reach more believers.